Artificial Intelligence in Manufacturing and Processing: A Comprehensive Review of Applications and Future Trends - Muhammad Mohsin Kabeer (CV. Shofanah Media Berkah, 2024)
The renewed strength of Friday robots in the production and processing of products is happening with the assistance of Artificial Intelligence (AI), and the intelligent review becomes fiercer and more ground-breaking. This review reviews the most important concepts of AI and points out the ways it is applied to production planning and predictive maintenance, quality control, robotics, and supply chain optimization. In processing, AI is used in developing processes, monitoring in-situ and safety standards in pharmaceutical, chemical and food companies. The examples of the best companies are the real cases to prove the effectiveness of the improvement of the productivity, quality, and sustainability. Beside its capability to change the world, the implementation of AI is confronted with problems of data quality, cost of implementation, lack of skills in the labor force and ethics. The additional new trends described in the review are explaining AI, edge AI, hyper automation, and sustainable AI practices. Overall, the article notes that the journey to AI integration is not easy, yet it is the important step towards having robust, adaptive, and future-sustaining industrial systems.